Development of algorithm to protect user communication devices against data leaks - Задерейко, Олександр Владиславович; Задерейко, Александр Владиславович; Zadereyko, Olexandr V.; Прокоп, Юлія Віталіївна; Прокоп, Юлия Витальевна; Прокоп, Ю. В.; Prokop, Yuliia V.; Трофименко, Олена Григорівна; Трофименко, О. Г.; Трофименко, Елена Григорьевна; Trofymenko, Olena H.; Логінова, Наталія Іванівна; et al. (Technology Center, 2021)
In order to identify ways used to collect data from user communication devices, an analysis of the interaction between DNS customers and the Internet name domain space has been carried out. It has been established that the communication device's DNS traffic is logged by the DNS servers of the provider, which poses a threat to the privacy of users. A comprehensive algorithm of protection against the collection of user data, consisting of two modules, has been developed and tested. The first module makes it possible to redirect the communication device's DNS traffic through DNS proxy servers with a predefined anonymity class based on the proposed multitest. To ensure a smooth and sustainable connection, the module automatically connects to a DNS proxy server that has minimal response time from those available in the compiled list. The second module blocks the acquisition of data collected by the developers of the software installed on the user's communication device, as well as by specialized Internet services owned by IT companies. The proposed algorithm makes it possible for users to choose their preferred level of privacy when communicating with the Internet space, thereby providing them with a choice of privacy level and, as a result, limiting the possibility of information manipulation over their owners. The DNS traffic of various fixed and mobile communication devices has been audited. The analysis of DNS traffic has enabled to identify and structure the DNS requests responsible for collecting data from users by the Internet services owned by IT companies. The identified DNS queries have been blocked; it has been experimentally confirmed that the performance of the basic and application software on communication devices was not compromised.

З метою виявлення шляхів збору даних з пристроїв комунікації користувачів було проведено аналіз взаємодії клієнтів DNS з доменним простором імен Інтернет. Встановлено, що DNS трафік пристрою комунікації журналюється DNS серверами провайдера, що саме по собі несе загрозу приватності користувачів. Розроблено та апробовано комплексний алгоритм захисту від збору даних користувачів, який складається з двох модулів. Перший модуль дозволяє перенаправити DNS трафік пристрою комунікації через DNS проксі-сервери з заданим класом анонімності, визначеним на основі запропонованого мультитесту. Для забезпечення безперебійного і сталого з'єднання модуль здійснює автоматичне підключення до DNS проксі-сервера з мінімальним часом відгуку з доступних у сформованому списку. Другий модуль блокує збір даних, який здійснюється розробниками програмного забезпечення, встановленого на пристрої комунікації користувача, та спеціалізованими інтернет-сервісами, які належать IT-компаніям. Запропонований алгоритм дозволяє користувачам вибирати бажаний рівень приватності при здійсненні комунікації з інтернет-простором. Це дозволяє знизити ймовірність цифрового профілювання пристроїв комунікації і, як наслідок, позбавити можливості інформаційних маніпуляцій над їх власниками. Проведено комплексний аудит DNS трафіка різних стаціонарних і мобільних пристроїв комунікації. Аналіз DNS трафіка дозволив ідентифікувати і структурувати DNS запити, які відповідають за збір даних користувачів інтернет-сервісами, що належать IT-компаніям. Виконано блокування ідентифікованих DNS запитів й експериментально підтверджено відсутність втрат працездатності базового і прикладного програмного забезпечення на пристроях комунікації користувача.

Для выявления путей сбора данных с устройств коммуникации пользователей проведен анализ взаимодействия клиентов DNS c доменным пространством имен Интернет. Установлено, что DNS трафик устройства коммуникации журналируется DNS серверами провайдера, что само по себе несет угрозу приватности пользователей. Разработан и апробирован комплексный алгоритм защиты от сбора данных пользователей, состоящий из двух модулей. Первый модуль позволяет перенаправить DNS трафик устройства коммуникации через DNS прокси-сервера с заданным классом анонимности, определяемым на основе предложенного мультитеста. Для обеспечения бесперебойного и устойчивого соединения модуль осуществляет автоматическое подключение к DNS прокси-серверу, имеющему минимальное время отклика из доступных в сформированном списке. Второй модуль блокирует сбор данных, собираемых разработчиками программного обеспечения, установленного на устройстве коммуникации пользователя, и специализированными интернет-сервисами, принадлежащими IT-компаниям. Предложенный алгоритм позволяет пользователям выбирать предпочитаемый уровень приватности при осуществлении коммуникации с интернет-пространством, тем самым обеспечивая им выбор уровня приватности и, как следствие, ограничить возможность информационных манипуляций над их владельцами. Проведен аудит DNS трафика различных стационарных и мобильных устройств коммуникации. Анализ DNS трафика позволил идентифицировать и структурировать DNS запросы, отвечающие за сбор данных пользователей интернет-сервисами, принадлежащими IT-компаниям. Выполнена блокировка идентифицированных DNS запросов и экспериментально подтверждено отсутствие потерь работоспособности базового и прикладного программного обеспечения на устройствах коммуникации.
Zadereyko А. Development of algorithm to protect user communication devices against data leaks / A. Zadereyko, Y. Prokop, O. Trofymenko, N. Loginova, О. Plachinda // Eastern-European Journal of Enterprise Technologies. – V. 1/2 (109) – Technology Center, 2021. – Р. 24-34.
Keywords: DNS query; DNS server; DNS leaks; DNS traffic; DNS proxy server; data collection; DNS запит; DNS сервер; витоки DNS; DNS трафік; DNS проксі-сервер; збір даних; DNS запрос; DNS сервер; утечки DNS; DNS трафик; DNS прокси-сервер; сбор данных; Research Subject Categories::TECHNOLOGY::Information technology